Bad times, big crimes - Keene, Carolyn (New York : Aladdin Paperbacks, 2005)
Nancy Drew finds herself in the 1930s, solving a crime that occurred during the Great Depression.
"Nancy Drew 75th anniversary."
008-012.
Accelerated Reader AR
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Time travel -- Fiction; Mystery and detective stories; Mystery fiction